Pengaruh Penerapan Green Accounting, Material Flow Cost Accounting, Corporate Social Responsibility, Envinronmental Disclosure Dan Envinronmental Performance Terhadap Sustainable Development - Najwan Malika; Rina Trisnawati (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to examine the effect of Green Accounting, Material Flow Cost Accounting (MFCA), Corporate Social Responsibility (CSR), Environmental Disclosure, and Environmental Performance on Sustainable Development in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. This study uses a quantitative approach with secondary data obtained from annual reports and company annual reports. The resulting sample was 79 and was selected through a purposive sampling technique with certain criteria, such as involvement in the PROPER program and publication of desire reports. The data were analyzed using SPSS with descriptive analysis stages, classical assumption tests, F tests, customized R², and t tests. The results showed that of the five independent variables tested, only Environmental Disclosure had a significant effect on Sustainable Development, while the other variables did not show a significant effect. This finding shows the importance of environmental information transparency in supporting sustainable development.